Thoracic surgery techniques of Serefeddin Sabuncuoğlu in the fifteenth century - BATIREL, HASAN FEVZİ (My University, 1997)
Serefeddin Sabuncuoğlu (1385 to 1470?) is known to be the author of the first surgery textbook, namely Cerrahiyyet'ül Haniyye (Imperial Surgery), written in Turkish in 1465. It is the first book to contain colored illustrations of surgical procedures, incisions, and instruments in the Turkish-Islamic medical literature. He was the first man to illustrate and mention introduction of a tube into the pharynx and upper esophagus, removal of foreign bodies in the esophagus by special instruments of his own design, and use of a silver ringlet in a man after tracheotomy. He also described and illustrated reduction of sternal fractures, thoracic puncture through the intercostal space for drainage of empyema cavities, and treatment of rib fractures that have severed the diaphragm. He was a humble, curious, and intelligent surgeon, and also a calligrapher and a miniature artist.
Keywords: Humans; Turkey; History, 15th Century; Thoracic Surgery; Textbooks as Topic